Host–virus interactions during infection with a wild-type ILTV strain or a glycoprotein G deletion mutant ILTV vaccine strain in an ex vivo system - Gayathri Gopakumar; Mauricio J.C. Coppo; Andrés Diaz-Méndez; Carol A. Hartley; Joanne M. Devlin (Microbiology Spectrum)
ABSTRACT Previous studies have demonstrated the safety and efficacy of a live-attenuated glycoprotein G (gG) deletion mutant vaccine strain of ILTV (∆gG-ILTV). In the current study, transcriptional profiles of chicken tracheal organ cultures (TOCs), 24 h post inoculation with ∆gG-ILTV or the gG-expressing parent wild-type strain, CSW-1 ILTV were explored and compared with the mock-infected TOCs using RNA-seq analysis. Transcriptomes of the vaccine and wild-type ILTV were also compared with each other. Although no viral genes (except for gG) were differentially regulated between the two ILTV-infected TOCs, pair-wise comparison of the transcriptomes of the ∆gG-ILTV or the CSW-1 ILTV-infected TOCs (each compared with mock-infected TOCs) identified the similarities and differences in host gene transcription between them. Several immune checkpoint inhibitors with likely roles in ILTV-mediated immune augmentation, and gene ontologies indicating cytokine response, and cytokine signaling were upregulated in both TOCs. Additionally, several other biological processes, molecular functions, and cellular components were enriched uniquely in the ∆gG-ILTV-infected TOCs, including those that indicated modifications to tracheal extracellular matrix (ECM) structural components, which may have a role in immune modulation in vivo. This study has revealed that the modifications of transcription of host genes during the early stages of ILTV infection are not limited to changes in cytokine or chemokine gene transcription, but several other immune-related genes and ECM components. Moreover, their differential regulation in the ex vivo system appears to be influenced by gG expression, potentially affecting the outcome of ILTV infection in vivo.IMPORTANCEInfectious laryngotracheitis virus (ILTV) remains a serious threat to poultry industries worldwide, causing significant economic losses. The glycoprotein G (gG) of ILTV is a virulence factor and a chemokine-binding protein with immunoregulatory functions. The influence of gG on the transcription of select host chemokine and cytokine genes has been demonstrated previously. This study extends our understanding of the early and localized host–ILTV interactions using genome-wide transcriptome analysis of ILTV-infected chicken tracheal organ cultures, and the role of gG during the process. Differential regulation of genes encoding immune checkpoint inhibitors observed in this study may have a role in ILTV-induced inhibition of type I interferon response, or negative regulation of T cell responses, bringing clarity to these ILTV immune-evasion mechanisms. Furthermore, differential regulation of genes encoding certain structural components and receptors with roles in cell migration, in the absence of gG, is consistent with the immunomodulatory role of ILTV gG.